Affective Mobile Language Tutoring System for Supporting Language Learning - Wu, Chih Hung; Lin, Hao-Chiang Koong; Wang, Tao-Hua; Huang, Tzu-Hsuan; Huang, Yueh-Min (Frontiers in Psychology, 2022)
Emotions play a significant role in everyday activities, in turn influencing attitudes, memory, decision-making, attention, learning, and learning achievement. Therefore, for the purposes of this study, an innovative Affective Mobile Language Tutoring System (AMLTS) was designed to support Japanese language learning. The effects of an AMLTS with asynchronous discussion intended to improve learning performance is examined using a triangulation method. In order to investigate the emotion effect, the proposed AMLTS provides a virtual emotion agent that can interact with users and then record emotional events, learning assessments, and the results of interaction into a database. Learning effectiveness evaluations were conducted in two experiments: a prototype evaluation and a final evaluation. Sixty-three beginner students were invited to use the AMLTS to learn Japanese. The research results showed that the proposed AMLTS affective interaction design significantly improve learner engagement and performance. In the emotion feedback analysis and learning process, the AMLTS helped students deepen their understanding of the learning content, to clearly understand the content, and to engage in peer interaction and experience positive emotions. In the evaluation of system usability, the AMLTS reveals good usability for foreign language acquisition.